The fecundity and prepotency of Show Yard cattle. - Milham, James Arthur (My University, 1907)
Introduction: The interest taken in exhibiting live stock can be observed by comparing the entries at the principal shows of the past season. The number of animals entered for the shows this past season was far in advance of the previous season. Thus we see competition is constantly growing stronger as the number of entries for each class increases, which has a tendency to raise the standard of the breed. In order to win, an animal must possess quality, character, breed type, and be in good show condition, which, at the present time, happens to be, "Carry a great deal of flesh." The judges will invariably place the blue ribbon on ananimal which has been highly finished but lacking somewhat in quality, character and breed type, and turn another animal of superior quality, character and breed type down, because it is not carrying quite enough flesh. We are not condemning the great amount of fat in all cases, but where an animal possesses quality, character and breed type, we see no reason why this animal should not be given the preference, although it does not possess so great an abundance of fat. The old maxim, "Fat covereth a multitude of sins," comes into play just at this time. In a breeding animal which has a great covering of fat, the judge is not able to detect defects. This animal, after the show season, will go back to the breeding pen and transmit these defects to its offspring, leaving the advancement of the breed, so far as this animal is concerned, at a standstill,or, possibly on a decline. The fecundity and prepotency of the show herd has been an obstacle in the way of success to many cattle breeders ever since cattle were first shown. Several instances are on record of animals of superior show-yard merit, which never left any legacy, aside from their show-yard triumphs, to the breed which they represent. Why there should have been so many cattle reported as non-breeders or shy-breeders, is the object of this discussion.
Citation: Milham, James Arthur. The fecundity and prepotency of Show Yard cattle.. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Show Yard Cattle; Live Stock; Live Stock Shows; Theses